2020
DOI: 10.1039/c9lc01209e
|View full text |Cite
|
Sign up to set email alerts
|

Development of two-photon polymerised scaffolds for optical interrogation and neurite guidance of human iPSC-derived cortical neuronal networks

Abstract: We identified photopolymers for 2-photon polymerisation with biocompatibility for human iPSC-derived neural network development. Generation of microscale scaffold topologies enabled neurite guidance, demonstrating use in reproducing aligned networks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 96 publications
(122 reference statements)
0
17
0
Order By: Relevance
“…Triangles: The triangle-shaped obstacles were designed to mimic the geometry of experimental scaffold structures (Crowe et al, 2020 ). Triangles were of isosceles shape with 50 μm height and 20 μm width.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Triangles: The triangle-shaped obstacles were designed to mimic the geometry of experimental scaffold structures (Crowe et al, 2020 ). Triangles were of isosceles shape with 50 μm height and 20 μm width.…”
Section: Methodsmentioning
confidence: 99%
“…They were designed to facilitate the trapping or deflection of axons (crosses), to gently modulate connectivity across the network (circles) and to dictate the directionality of connectivity (triangles). We selected these shapes in view of recent experimental studies aimed at guiding neuronal connectivity through microfabrication technology (Crowe et al, 2020 ). We observed that the obstacles molded structural connectivity at short and long length scales.…”
Section: Introductionmentioning
confidence: 99%
“…Calcium imaging experiment, as adapted from Ozdener et al [ 12 ], was, accordingly, performed to investigate whether cultured BTBCs still retain their physiological functions of taste responsiveness post their isolation and cryopreservation. The dynamic calcium imaging experiments were conducted and analysed according to standard approaches used in our laboratory [ 18 , 19 ]. Cells were exposed for 50–100 ms depending on loading efficiency of particular culture, this was kept constant for each experiment.…”
Section: Methodsmentioning
confidence: 99%
“…In most biocompatible photoresist systems such as hydrogel-based natural or artificial materials, they also need to be soluble and thermally stable in the monomer aqueous microenvironments [42]. Currently, a lot of PIs, such as rose bengal, methylene blue, lithium phenyl-2,4, 6-trimethyibenzoylphosphinate (LAP) and Irgacure 369, are available commercially and commonly used for fabricating micro/nano-structures for biomedical applications [26,36,[50][51][52]. In Table 1, PIs for the TPP fabrication are summarized along with their water solubility, δ TPA , and biomedical applications as reported in some studies.…”
Section: Introductionmentioning
confidence: 99%